Implementation of Rent-to-Own Flats Management at Ngelom Rental Flats, Sidoarjo Regency - Auditya Desvananda Putra Purwanto (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study aims to analyze the implementation of rental flats in the Ngelom simple rental flats (rusunawa), Sidoarjo Regency using the Van Meter and Van Horn policy implementation model. This study was motivated by various problems such as payment arrears, violations of rules by residents, and lack of resources that hinder optimal management of rusunawa. The research method used is descriptive qualitative, with data obtained through interviews, observations, and documentation. The analysis was carried out based on six indicators in the Van Meter and Van Horn model, namely (1) policy standards and targets, (2) resources, (3) inter-organizational communication, (4) implementor tendencies, (5) character of implementing agents, (6) social, economic, and political conditions. The results of the study indicate that although the management policy has clear standards and objectives, its implementation still faces various obstacles. Lack of staff and financial resources are the main obstacles, while the social conditions of residents who are less disciplined worsen the situation. On the other hand, communication between organizations is going well, although the tendencies and characters of implementers still need to be improved. From the results of the study it can be concluded that the implementation of the Ngelom Rusunawa management has not been carried out optimally.  Keywords: Flats, Implementation, Management.